Acremonidins F–H and acremoxanthones F–G, antimicrobial substances from the insect fungus Verticillium sp. BCC33181. Issue 10 (10th March 2016) - Intaraudom, Chakapong; Bunbamrung, Nantiya; Dramae, Aibrohim; Boonyuen, Nattawut; Komwijit, Somjit; Rachtawee, Pranee; Pittayakhajonwut, Pattama
Abstract: Six new compounds, including three acremonidins F–H (1, 3, and5 ), two acremoxanthones F–G (7 and8 ), and acremonoxide (10 ), along with eight known compounds (2, 4, 6, 9, 11 –14 ) were isolated from Verticillium sp. BCC33181. Their structures were determined based on extensive 1D and 2D NMR spectral analyses, mass spectrometric data and by comparison with the known compounds reported previously. The relative configurations were identified based upon NOESY spectroscopic information as well as comparison of CD spectrum with the known analogs. Both acremonidins and acremoxanthones exhibited anti- Bacillus cereus activity (MIC 0.39–25 μg/mL), while acremonidins F (1 ), A (2 ), G (3 ), and C (4 ) also displayed anti- Enterococcus faecium activity (MIC 1.56–25 μg/mL). In addition, acremoxanthones F (7 ) and G (8 ) showed antimalarial activity against Plasmodium falciparum K1 strain, multidrug–resistant strain, with respective IC50 values of 2.38 and 1.71 μg/mL, while others were inactive. Graphical abstract: